Associations of smoking and air pollution with peripheral blood RNA N6-methyladenosine in the Beijing truck driver air pollution study - Kupsco, Allison; Gonzalez, Gwendolyn; Baker, Brennan H.; Knox, Julia M.; Zheng, Yinan; Wang, Sheng; Chang, Dou; Schwartz, Joel; Hou, Lifang; Wang, Yinsheng; Baccarelli, Andrea A. (Environment international, 2020)
•Men that smoked had lower total peripheral blood RNA m6A levels than male nonsmokers.•Total blood RNA m6A was positively associated with 8-hour black carbon exposure.•Blood m6A reader, writer and eraser mRNA levels were not associated with exposures.•Global m6A levels were not correlated with reader, writer and eraser mRNA levels. Post-transcriptional modifications of RNA constitute fundamental mechanisms of gene regulation. N6-methyladenosine (m6A) is critical for health and disease and is modulated by cellular stressors. However, associations between environmental exposures and m6A have not been studied in humans. We aimed to examine associations between tobacco smoking and particulate air pollution with m6A and mRNA expression levels of its reader, writer and eraser (RWE) genes in blood. Using the Beijing Truck Driver Air Pollution Study, we investigated global m6A in RNA from peripheral blood collected from 106 human subjects in Beijing, China, in 2008. We measured m6A with nano-flow liquid chromatography-tandem mass spectrometry and investigated gene expression of six m6A RWEs with real-time-quantitative PCR. Using linear models, we examined associations with smoking status, pack-years, and smoking on day of visit in men, and with environmental tobacco smoke in nonsmokers. We also examined associations with ambient PM10 (particulate matter ≤ 10 µm in diameter), and personal black carbon (BC) and PM2.5 measured with a portable monitor. Smoking in men was significantly associated with a relative 10.7% decrease in global m6A levels in comparison to nonsmokers (p = 0.02). In men, smoking greater than 3.8 pack-years was associated with a 14.9% lower m6A than in nonsmokers. BC exposure trended towards positive associations with m6A (5.95% per 10 μg/m3 increase in BC; 95% CI: −0.96, 13.3). Global m6A levels were not correlated with RWE gene expression levels. No associations were detected between smoking or air pollutants and m6A RWE gene expression. m6A was negatively associated with long-term smoking, yet positively associated with short-term BC exposure. These results indicate variable m6A responses to environmental stressors, providing early evidence into the impacts of toxicants on RNA modifications and suggesting potential for m6A as a biomarker or mechanism in environmental health research.